MOTIVASI PENGUSAHA INDUSTRI MAKANAN DAN MINUMAN HALAL TERHADAP PEMBIAYAAN PERBANKAN SYARIAH DI KOTA BANDA ACEH DAN KABUPATEN ACEH BESAR - De-Erista Mirati Putri; Sartiyah Sartiyah (JURNAL ILMIAH MAHASISWA EKONOMI ISLAM, 2020)
This study aims to analyze the knowledge, lifestyle, promotion and product quality on the decisions of halal food and beverage industry entrepreneurs in using Islamic banking financing in the City of Banda Aceh and Aceh Besar Regency. This research is a quantitative study using a questionnaire to the halal food and beverage industry entrepreneurs. The population of halal food and beverage industry entrepreneurs in this area obtained 119 and using the Slovin method obtained a sample of 68 respondents. The method of data analysis uses binary logistic regression. The results showed that simultaneous knowledge, lifestyle, promotion, and product quality affect financing in Islamic banking. Partially lifestyle and product quality have an effect, while knowledge and promotion have no effect on the entrepreneur's decision to use financing in Islamic banking. Odd ratio results indicate that the entrepreneurial lifestyle and product quality have a greater influence on the use of financing in Islamic banking than the use of credit in conventional banking.